2015
DOI: 10.1161/hypertensionaha.115.05484
|View full text |Cite
|
Sign up to set email alerts
|

Classical Complement Pathway Activation in the Kidneys of Women With Preeclampsia

Abstract: A growing body of evidence suggests that complement dysregulation plays a role in the pathogenesis of preeclampsia. The kidney is one of the major organs affected in preeclampsia. Because the kidney is highly susceptible to complement activation, we hypothesized that preeclampsia is associated with renal complement activation. We performed a nationwide search for renal autopsy material in the Netherlands using a computerized database (PALGA). Renal tissue was obtained from 11 women with preeclampsia, 25 pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 49 publications
(62 reference statements)
2
37
0
Order By: Relevance
“…These findings link the pathogenesis of glomerular TMA associated with anti-VEGF therapy to that of complement-mediated aHUS and may explain why the renal glomerulus is susceptible to complement-mediated disease. Interestingly, preeclampsia, another glomerular disease associated with endotheliosis and caused by chronic VEGF inhibition secondary to increased soluble VEGFR1, is also associated with complement activation (58, 59), suggesting that this work may also be relevant to this disease.…”
Section: Discussionmentioning
confidence: 99%
“…These findings link the pathogenesis of glomerular TMA associated with anti-VEGF therapy to that of complement-mediated aHUS and may explain why the renal glomerulus is susceptible to complement-mediated disease. Interestingly, preeclampsia, another glomerular disease associated with endotheliosis and caused by chronic VEGF inhibition secondary to increased soluble VEGFR1, is also associated with complement activation (58, 59), suggesting that this work may also be relevant to this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The complement system includes a variety of complement components and some of them have been reported to be associated with PE [22][23][24][25][26]. Upon activation of the complement cascade, the formation of C3 and C5 convertase results in the cleavage of the complement component C5 to C5a and C5b.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies demonstrated significantly enhanced systemic complement system activation in preeclamptic pregnancies compared to normal pregnancies (Derzsy et al, 2010; Regal et al, 2015a). Both the placenta and kidney also showed evidence of increased local complement activation in preeclampsia, coincident with up-regulation of message for complement regulators but no evidence of changes in regulator expression using immunohistochemistry have been reported (Burwick et al, 2014; Buurma et al, 2012; Lokki et al, 2014; Penning et al, 2015). However, the event or events that initiate complement activation in preeclampsia are unknown.…”
Section: Introductionmentioning
confidence: 97%